Diagnosed child, treated child: food challenge as the first step toward tolerance induction in cow's milk protein allergy. - Longo, G; Berti, I; Barbi, E; Calligaris, L; Matarazzo, L; Radillo, O; Ronfani, L; Ventura, A (Eur Ann Allergy Clin Immunol, 2012)
BACKGROUND: Food challenge is required to assess tolerance in cow milk (CM) allergy. A positive challenge contraindicates the reintroduction of CM. Specific oral tolerance induction (SOTI) is a promising treatment. METHODS: All children admitted for a challenge were prospectively enrolled. To those tolerating between 2 and 150 ml a SOTI protocol was offered. Outcome, adverse reactions, parents' satisfaction were recorded. RESULTS: Out of 245 challenged patients, 175 reacted 122 out of 125, able to tolerate a minimum dose of 2 ml, underwent SOTI. After one year 75.4% were in an unrestricted diet, 16.1% tolerated between 5 and 150 ml, 8.5% stopped SOTI. Side effects were mild, parents' satisfaction was very high. CONCLUSIONS: The majority of children tolerating limited amounts of CM at the challenge acquires tolerance with SOTI without relevant side effects. Maintaining on an exclusion diet partially tolerant children should be considered debatable.
Keywords: Administration, Oral; Adolescent; Animals; Cattle; Child; Child, Preschool; Humans; Immune Tolerance; Infant; Milk Hypersensitivity; Milk Proteins; Self Administration